2014
DOI: 10.1016/j.jallcom.2013.10.234
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hardening of Zr2Co11:(Ti, Si) nanomaterials

Abstract: The role of Ti and Si additions in the magnetic hardening of rapidly quenched Zr2Co11-based nanomaterials has been investigated. Nanocrystalline Zr17-xTixCo83 and Zr18Co82-ySiy are mainly composed of rhombohedral Zr2Co11 and a small amount of orthorhombic Zr2Co11, hcp Co, and cubic Zr6Co23. Ti addition decreases the mean grain size of the magnetic phases, and thus increases coercivity and energy product from 1.6 kOe and 1.9 MGOe for x = 0 to 2.6 kOe and 3.9 MGOe for x = 2, respectively. Si addition enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Metallic additives such as Ti, Si or Mo facilitate the formation of the hard-magnetic phase and decreases both the mean grain size and the amount of the soft Co phase. 5,[10][11][12] The addition of Si and B has a similar effect. 3 In particular, boron addition has been found to increase the coercivity of rapidly quenched Zr-Co materials, 13,14 but it is unclear how B addition affects the phase components and structural properties.…”
Section: Introductionmentioning
confidence: 88%
“…Metallic additives such as Ti, Si or Mo facilitate the formation of the hard-magnetic phase and decreases both the mean grain size and the amount of the soft Co phase. 5,[10][11][12] The addition of Si and B has a similar effect. 3 In particular, boron addition has been found to increase the coercivity of rapidly quenched Zr-Co materials, 13,14 but it is unclear how B addition affects the phase components and structural properties.…”
Section: Introductionmentioning
confidence: 88%
“…The lattice parameters of Zr2(Co,Mo,Si,B)11 for two samples are a = b = 4.7866 and c = 11.7658 Å. The cell volume is 233.46 Å 3 , which is much smaller than that of Zr2Co11, which indicates that the smaller B and Si atoms occupy Zr2Co11 lattice sites [10,13] It has been reported that the existence of dislocations is a prerequisite to launch recrystallization which often leads to a change of grain orientation, grain growth, and decrease of defect density. [14,15] Earlier work showed that dislocations were observed in nanocrystalline Zr2Co11 materials.…”
Section: Resultsmentioning
confidence: 95%
“…[8] Ti addition suppressed the formation of Zr2Co11 dendrites upon solidification, refined the structure, and enhanced the coercivity. [9,10] A high coercivity of 6.7 kOe was achieved for the as-spun Zr2Co11-based nanocomposites with the additions of Si and B. [11] The coercivity was further increased up to 7.9 kOe for the single-phase Zr2Co11 alloy due to Mo addition.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the thermal behaviors of these two structures have not been deeply investigated although the cooling rate strongly affected the magnetic properties [8][9][10]. In current, many researches have focused to increase the hard magnetic properties of the Zr2Co11 alloy through adding additional substitutional or interstitial elements for modifying the lattice parameter and changing the alloy composition of as-spun ribbons [11][12][13][14]. However, there is few papers on the annealing behaviors of asquenched ribbons that affect the crystallinity and the grain size of the Zr2Co11 phase.…”
Section: Introductionmentioning
confidence: 99%